2012
DOI: 10.1055/s-0032-1306776
|View full text |Cite
|
Sign up to set email alerts
|

Propofol sedation with bispectral index monitoring is useful for endoscopic submucosal dissection: a randomized prospective phase II clinical trial

Abstract: Propofol with BIS monitoring improved recovery of patients after ESD, though this study was underpowered to prove the effectiveness and safety of propofol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 20 publications
1
51
0
1
Order By: Relevance
“…Propofol sedation is widely used for gastrointestinal tract endoscopy in Western countries, but its use in endoscopic practices in Japan is uncommon, because administration of propofol by endoscopists is very restricted because of a government regulation and anesthesiologists rarely come to an endoscopy unit. However, we recognize the use seems to be convenient and safe from two studies [12,13]. The evidence will hopefully lead to common use of propofol sedation for, at least, therapeutic endoscopy, including gastric ESD, in Japan.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Propofol sedation is widely used for gastrointestinal tract endoscopy in Western countries, but its use in endoscopic practices in Japan is uncommon, because administration of propofol by endoscopists is very restricted because of a government regulation and anesthesiologists rarely come to an endoscopy unit. However, we recognize the use seems to be convenient and safe from two studies [12,13]. The evidence will hopefully lead to common use of propofol sedation for, at least, therapeutic endoscopy, including gastric ESD, in Japan.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies regarding propofol sedation (one RCT and one case series study) were identified [12,13]. Sasaki et al [12] revealed that propofol had modest advantages over midazolam in terms of safety and efficacy during ESD, but significantly earlier recovery from sedation was obtained in the propofol group.…”
Section: Preparation and Sedationmentioning
confidence: 99%
See 1 more Smart Citation
“…The BIS is also used for sedation assessment in critically ill patients (11)(12)(13)(14)(15)(16). Although the BIS has not been developed for use in patients with neurologic disorders, some published studies have focused on brain injured patients (17)(18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…The bispectral index (BIS), an objective assessment tool for the prevention of intraoperative awareness during general anesthesia, has also recently been used to evaluate sedation levels. [6][7][8][9] However, mainly because of the high cost of BIS, it is not standard equipment for sedation during dental treatment.…”
mentioning
confidence: 99%